Comunicação e marketing : um estudo das interações comunicacionais entre feirantes e fregueses na feira livre de Paripiranga-BA - Ferreira, Thales Brandão (2017)
Despite the modernization of retail and urban growth, free trade shows continue to be a space of sociability in an economic, social and cultural dynamic. The central problem of the research was to understand if the communication interactions adopted by the FLV (fruits, vegetables and greens) marketers have influenced the perception of the customers under the market compound, in the free fair of Paripiranga-BA. The city fair takes place on Tuesdays and Fridays, and the configuration of this work is limited to researching the marketers and shoppers who circulate in commerce earlier in the week, that is, on Tuesdays. The fundamental hypothesis of the work, oriented to the marketers selling fruits and vegetables was due to the preference of the customers for free markets, to have the belief that the foods sold there are always fresh and of superior quality, besides being negotiable. This space of commerce is generally the heart of the fair, place of greater flow of customers and with a high degree of communication and marketing. The justification for studying this outdoor trade comes from its historical representativeness through symbolic elements that reflect the memory and cultural value of the region, also highlighting the commercial movement, since the city is located on the border between Sergipe and Bahia, A large number of marketers from the surrounding regions of the two States. The main objective of the research was to evaluate the communication interactions of the fruit, vegetable and greens vendors (FLV), at the point of sale, based on the perception of the customers before the market compound, at the free fair of the city of Paripiranga-BA. The theoretical framework of marketing management (marketing concept, customer value, marketing compound, commodities and service marketing) and communication (questions of communication interactions: popular, verbal and non-verbal) was adopted for this clipping. Methodologically, participant observation techniques and interviews were carried out. It was a 15-month ethnographic study of the marketing and communications practices of 8 (eight) marketers with anthropological perspective (sociability, photographs and notes in field journals) and an analysis of the consumption behavior of 65 (sixty five) customers. The results obtained through observation, dialogue with the marketers and records of images revealed that verbal communication through orality becomes more evident in the negotiation process, modifying the way of communicating, organizing and selling, because the products Commercialized in the segment of FLV (fruits, vegetables and greens) are not fresh due to the movement of the fair to other fairs.